INVESTMENT, LABOR AND THEIR EFFECTS ON ECONOMIC GROWTH OF PONOROGO REGENCY - Winanto, Asis Riat (Universitas Muhammadiyah Ponorogo, 2019)
The condition of a well-developed and rapid economy is not the best guarantee for economic growth if it is not followed by increased employment opportunities and increased investment. This can be understood because with the increase in employment opportunities will be able to accommodate new workers who each year has increased. Therefore, population growth in an economy/region must be balanced with an increase in employment opportunities so that the existing workforce can be absorbed in the world of work. Besides that, there are also conditions that must be met for development and economic growth in order to run well (experiencing an increase), namely the existence of investment activities. It is expected that an increase in investment activities, then economic activities also increase, so that it will increase the economic growth of a region. The investment that takes place in Ponorogo Regency will certainly absorb a large number of workers. With these conditions will create economic activities in various sectors that are increasingly developing, and this will have an impact on increasing development and economic growth in Ponorogo Regency. From the results of the significance test in the level of error of 5%, it can be seen that the investment does not affect the growth of the economy of Ponorogo Regency. However, if viewed from the regression equation, it turns out there is an influence of investment on economic growth, although the effect is relatively small. So that high investment will also be able to increase economic growth in Ponorogo Regency. While labor has an influence on the economic growth of Ponorogo Regency at a significance level of 5%. And from the regression equation, labor has a relatively high influence on economic growth. And from the simultaneous test, it is proven that investment and labor together influence the economic growth of Ponorogo Regency.